Karaj and its relations with the neighboring powers (500-658 AH / 1106-1260 AD) (Journal of the College of Basic Education, 2022)
The country of Karaj is located in the mountainous region of the Caucasus, and the Arabs were the first to call it this name. And the Kurds continued to be committed to the covenant until they felt the weakness of the Islamic state at the beginning of the sixth century AH due to internal conflicts, and they made an alliance with other forces hostile to Muslims. Karaj pilgrims